2019
DOI: 10.3389/fpsyg.2019.02151
|View full text |Cite
|
Sign up to set email alerts
|

The Seed of Goal-Related Doubts: A Longitudinal Investigation of the Roles of Failure and Expectation of Success Among Police Trainee Applicants

Abstract: Various theories on personal goal striving rely on the assumption that failure raises doubts about the goal. Yet, empirical evidence for an association between objective failure experiences and doubts about personal long-term goals is still missing. In a longitudinal field study, applicants for a job as a police trainee (n = 172, Mage = 25.15; 55 females and 117 males) were accompanied across three measurement times over a period of five months. We investigated the effects of failure and initial expectation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…The present findings extend previous research by showing that doubts not only occur or dissolve after major failures (Bettschart et al, 2019) but also in reaction to mundane and frequent events in goal pursuit. The findings further reveal that individuals with higher (vs. lower) levels of action crisis experience more goal-related doubts during any activity.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present findings extend previous research by showing that doubts not only occur or dissolve after major failures (Bettschart et al, 2019) but also in reaction to mundane and frequent events in goal pursuit. The findings further reveal that individuals with higher (vs. lower) levels of action crisis experience more goal-related doubts during any activity.…”
Section: Discussionsupporting
confidence: 90%
“…Previous longitudinal studies examining the predictors of action crises have used a time frame of weeks or months. They found that individuals who experienced (vs. did not experience) failure in goal striving (Bettschart et al, 2019), appraised the attainability of their goal as being lower (vs. higher; Ghassemi et al, 2017), and had a more controlled (vs. autonomous) motivation for goal pursuit (Holding et al, 2017) experienced higher levels of action crisis. On an intraindividual level, a controlled motivation for goal pursuit (Holding et al, 2017) and appraisals of low goal attainability (but not goal desirability) predicted an increase in the action crisis (Ghassemi et al, 2017).…”
Section: Which Situational Factors Predict Doubts?mentioning
confidence: 99%
See 1 more Smart Citation
“…Given these negative consequences of experiencing an action crisis, it is important to identify possible antecedents. We start off with empirical evidence on the predictive power of goal-related difficulties for experiencing an action crisis (Bettschart et al, 2019 ; Ghassemi et al, 2017 , 2020 ). Specifically, we asked ourselves: Who is better in dealing with difficulties and thereby preventing action crises?…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the dynamics of goal pursuit also requires a longitudinal design in which observations of important process components (e.g., proximity to the goal and time to the deadline) can be made over time (Neal, Ballard, & Vancouver, 2017). However, the vast majority of research in this area has used either static, between-participant designs (Huang, Lin, & Zhang, 2019;Huang, Zhang, & Broniarczyk, 2012;Jia, Hirt, & Fishbach, 2019) or designs that incorporate only a small number of observations (e.g., five or fewer; Bettschart, Herrmann, Wolf, Brandstätter, & Healy, 2019;Lee, Sheldon, & Turban, 2003). Such designs are not well-suited for understanding the dynamics of goal pursuit because they tell us little about how the process plays out over time.…”
mentioning
confidence: 99%